Flexibility coefficient calculation of rubber tyred metro and its applicability analysis - DU Zixue; TANG Tian; YANG Zhen; LIAO Congjian (机车电传动)
The rubber tyred metro has three-series suspension systems and two sets of running systems, namely rubber wheels and steel wheels. The steel wheels, as safety wheels, only function in the event of tyre burst and turnout passing. In normal running, the steel wheels have no contact with the rail, so the calculation formula of the flexibility coefficient of rail vehicle derived in the past is no longer applicable to the rubber tyred metro. In view of the differences between the running systems of rubber tyred metro and railway vehicle, this paper deduced the calculation formula of the flexibility coefficient of the rubber tyred metro vehicle according to the definition of the flexibility coefficient in the UIC 505-5 regulation, and established the "vehicle-tyre-track beam" coupling dynamics simulation model of the rubber tyred metro vehicle by using the multi-body dynamics software ADAMS to verify the correctness of the formula. The calculated results were close to the simulation results. When the rubber tyred metro stopped on the inclined track with a superelevation rate of 11.15% in AW5 working condition, the value of the flexibility coefficient was the maximum and exceeded the limit value of 0.4 of the flexibility coefficient provided in the UIC 505-5 regulations. However, it could be judged that the rubber tyred metro was in a safe state at this time and did not overturn according to the tyre force and wheel load reduction rate. The results show that the derived formula for calculating the flexibility coefficient is consistent with the simulation results. However, due to the obvious difference between the conventional track structure and the rubber tyred metro vehicle, it is not suitable to use the limit value of the flexibility coefficient provided in the UIC 505-5 regulation and the flexibility coefficient to evaluate the anti-overturning ability of the rubber tyred metro vehicle in the AW5 working condition.